Analisis Faktor-faktor yang Mempengaruhi Perilaku Konsumen Terhadap Perilaku Pembelian Ikan Layang (decapterrus russelli) di Pelabuhan Perikanan Nusantara Brondong - Mujtahiddin, Muhammad Ihwanul; Kurriwati, Nirma (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The purpose of this research is to study the factors that influence asking to buy flying fish at the archipelago fishing port in Brondong sub-district, this research uses quantitative research methods using primary and secondary data sources. In this study using factor analysis techniques using SPSS version 25.0. The results of the study show that sequentially the factors that influence the decision to buy flying fish at PPN Brondong are distribution factors, product factors, price factors, professional factors, service factors, location factors, and nutritional factors, therefore the dominant factors in influencing fish buying decisions overpass in the Brondong PPN is the distribution factor.